PENGGUNAAN METODE UMMI DAN METODE AN-NAHDLIYAH UNTUK MENINGKATKAN KEFASIHAN SISWA DALAM PELAFALAN HURUF HIJAIYAH (STUDI FONOLOGI) - Nihayati, Aim Matun (STIQ Amuntai, 2023)
This study aims to analyze, understand, and describe: 1.) How to use the Ummi method at SD Muhammadiyah Wirobrajan 1 and an-Nahdliyah method at TPQ Nurul Anwar Rembang. 2.) What is the quality of the pronunciation of hijaiyah after applying the Ummi Method at Muhammadiyah Wirobrajan 1 Elementary School and an-Nahdliyah Method at TPQ Nurul Anwar Rembang. 3.) The differences between the Hijaiyah pronunciation Ummi method and the An-Nahdliyah method. This study uses the approach of descriptive qualitative—a collection of results through interviews, observation, and documentation. Data analysis techniques include data reduction, data presentation, and conclusions. The informants in this study were school principals, the Vice Chairman of Curriculum, students, and BTAQ teachers. The study's results used the Ummi method at Muhammadiyah Wiro 1 Elementary School to increase students' fluency in Hijaiyah pronunciation, which is not quite suitable because BTAQ teachers still need to be certified and are still in the mentoring process. And then use of the an-Nahdliyah method to increase students' fluency in pronouncing hijaiyah is maximized because the learning is carried out intensely.